PROFIT FUNCTION ANALYSIS OF DAIRY CATTLE FARMING IN GETASAN AND WEST UNGARAN DISTRICTS, SEMARANG REGENCY - Haloho, R.D.; Santoso, S.I.; Marzuki, S.; Roessali, W.; Setiadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The purpose of this study was to analyze the influence of the production factors on the profit of thedairy cattle farming business in Semarang regency. The research was conducted during July-September2012. The method used was a survey method. The sampling technique used multistage random samplingmethod. The selected locations (Getasan and West Ungaran District) were deliberately selected becausethey had the highest population of dairy cattle. Respondents were dairy cattle farmers who were drawnrandomly as many as 80 respondents. The measured variables were profit, cost of forage, cost ofconcentrate, cost of labor, capital and farm experience. The data were analyzed descriptively andstatistically. Data were analyzed using the profit function Output Unit Price Cobb-Douglas. Multiplelinear regression was used in the study. The research showed that the factors of production inputssimultaneously significantly affected farmers profit (P<0.05). Forage cost, concentrate feed cost, andcapital partially affected on farmer profit (P<0.05). The average production cost was IDR1,661,827/year. The average profit was IDR 2,399,453/month. The average revenue was IDR737.625/month with an average of lactation cattle scale ownership was 2.4 head/farmer. According tothe result, dairy cattle’s farming in Semarang Regency was profitable.